1999
DOI: 10.1038/sj.bjc.6690393
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and distribution of an oncofetal antigen (M2A antigen) expressed on testicular germ cell tumours

Abstract: M2A antigen is an oncofetal antigen associated with germ cell neoplasia, present in testis on fetal gonocytes and re-expressed on carcinoma in situ (CIS) and germ cell tumours. We developed a panel of monoclonal antibodies (mAb), M2A (IgG2a), D1-26 (IgG2b) and D2-40 (IgG1), to this antigen in order to characterize its structure and study its distribution among germ cell tumours. M2A antigen was purified by sequential lectin and antibody affinity chromatography and characterized as a monomeric M … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
208
0
7

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(220 citation statements)
references
References 27 publications
5
208
0
7
Order By: Relevance
“…The overall cellular distribution of the staining corresponded to the normal location of the M2A antigen (glycoprotein) on the cellular surface and within the Golgi complex. 12 One of 24 lesions was negative; however, this might have been due to the small size of the biopsy containing only one tumor lobule.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The overall cellular distribution of the staining corresponded to the normal location of the M2A antigen (glycoprotein) on the cellular surface and within the Golgi complex. 12 One of 24 lesions was negative; however, this might have been due to the small size of the biopsy containing only one tumor lobule.…”
Section: Resultsmentioning
confidence: 98%
“…12 The carbohydrate structure of the antigen recognized by D2-40 is common for mucin-type glycoproteins that are widely expressed in normal and tumor cells. 20 Thus, although M2A was initially identified in fetal gonocytes, germ-cell tumors, and prepubertal Sertoli cells, [21][22][23] it is also present in a number of human cancer cell lines, including osteosarcoma and transitional cell carcinoma.…”
Section: D2-40 In Kaposiform Hemangioendotheliomamentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the overexpression of this antigen, c-kit is rarely mutated in these tumors. Other antibodies, which immunoreact with IGCNU but are rarely used in clinical practice, include M2A and 43-F. 57,59,60 POU5F1 (Oct3/4) is a very interesting marker that was recently described. 61 The gene serves as a transcription factor and its product is expressed in pluripotent mouse and human embryonic stem cells and is downregulated during differentiation.…”
Section: Intratubular Germ Cell Neoplasiamentioning
confidence: 99%
“…23,24 D2-40 is a novel monoclonal antibody that was reported to recognize a 40 kDa surface sialoglycoprotein expressed in germ cell neoplasia and fetal testicular gonocytes. 25 A recent investigation has demonstrated that this mucin-type glycoprotein is podoplanin. 26 Martín-Villar et al 28 and Ma et al 27 both described its human genome.…”
mentioning
confidence: 99%